2012
DOI: 10.1016/j.whi.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Internet Message Boards for Pregnancy Loss: Who’s On-Line and Why?

Abstract: Background Pregnancy loss is a common event but its significance is often minimized by family, friends, and community, leaving bereaved parents with unmet need for support. This study sought to describe demographics, usage patterns, and perceived benefits for women participating in internet pregnancy loss support groups. Methods We requested permission to post an anonymous internet survey on large and active United States internet message boards for women with miscarriages and stillbirths. The study purposef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 19 publications
7
47
0
4
Order By: Relevance
“…Her own parents, by contrast, had made her feel "uncomfortable" [no.107: 27 months] about her stillbirth. For others, sympathetic others were found on web sites, blogs and chat rooms supporting the findings of Gold, Boggs, Mugisha, and Palladino (2012) who reported that in the US, internet sites could be an important source of support. Our study shows that websites and blogs were particularly used by those who also reported difficulties in making and sharing memories of their babies (see, e.g.…”
Section: Inhabiting Half Worlds: the Expert And The Wisesupporting
confidence: 69%
“…Her own parents, by contrast, had made her feel "uncomfortable" [no.107: 27 months] about her stillbirth. For others, sympathetic others were found on web sites, blogs and chat rooms supporting the findings of Gold, Boggs, Mugisha, and Palladino (2012) who reported that in the US, internet sites could be an important source of support. Our study shows that websites and blogs were particularly used by those who also reported difficulties in making and sharing memories of their babies (see, e.g.…”
Section: Inhabiting Half Worlds: the Expert And The Wisesupporting
confidence: 69%
“…In some cases, women felt freer to talk without becoming visibly emotional and without having to deal with the "pitying stares one can get face to face" (Gold et al, 2012, p. 70). The flexibility of accessing support anywhere at any time was also seen as an advantage to online message boards (Gold et al, 2012).…”
Section: Components To Consider When Developing a Support Groupmentioning
confidence: 99%
“…Those who experience such distressing symptoms often reach out to others for support and comfort (Wright, 2010). However, many perinatally bereaved women have reported that their grief was not adequately recognized by friends or family members (Gold, Boggs, Mugisha, & Palladino, 2012), which left them feeling emotionally abandoned.…”
Section: Introductionmentioning
confidence: 99%
“…Existem gastos econô-micos com a morte: despesas com funerais e investigação da causa, mas o maior custo é inatingível, pois está relacionado com tristeza, ansiedade e medo, o que evidencia a necessidade de estratégias de apoio a essa população (12)(13)(14).…”
Section: Introductionunclassified